Jenis-Jenis Paku Epifit di Hutan Desa Beginjan Kecamatan Tayan Hilir Kabupaten Sanggau - Irwan Lovadi, Weri Febri Lindasari, Riza Linda, (Universitas Tanjungpura, 2015)
Ferns have an important role in nutrient recycling at the communities and structure of the forest. The epiphytic fern is a small group of plants which is typical of a tropical rainforest. This research aimed to find out the types of epiphytic ferns in the forest of Beginjan Village, Tayan Hilir Sub-district, Sanggau Regency. The research was conducted from July 2014 to October 2014 in the forest area of Beginjan Village, Tayan Hilir Sub-district, Sanggau Regency. The samples were taken through the cruise sampling method. The results of this reserach discovered 14 species of epiphytic ferns consisting of 1 Class Polypodiopsida and 6 families. The Polypodiaceae was the most commonly found family followed by the Families Davalliaceae, Nephrolepidaceae, Aspleniaceae, Hymenophyllaceae, and Pteridaceae.